Threads That Become Tendrils: Exploring EDI in the Settler-Canadian Arts and Culture Sector - Bernicky, Shanice (Culture and Local Governance / Culture et gouvernance locale, 2023)
The settler-state of Canada continues to reconcile with the genocide of the original Indigenous custodians of the lands on which we operate, alongside the underserving and discriminating against racialized, black, disabled, and LGBTQ2+ peoples all while navigating a climate crisis, the proliferation of equity, diversity, and inclusion (EDI) nomenclature and plans permeates every social and financial sector. EDI initiatives, while called many names throughout history such as social inclusion and affirmative action, experienced a rise in creation in 2020 because of public outcries for the acknowledgement of systemic racial injustice and pressure to address this ongoing form of violence. Canada’s arts and culture sector is not immune from this scrutiny. Having a long history of engaging in social services, the arts and culture sector is often tasked with “fixing” issues when funding is cut to education, health, and community programs, yet arts institutions are not equipped to do this. This paper follows one resident researcher’s journey as they were tasked with developing an arts civic impact framework suggesting equity practices in the arts. The study used a mixed-methods approach, drawing from the walking interview, reverse photo-elicitation, feminist manifestos and research-creation to bring cultural workers across the country together to develop an accessible tool to carefully engage in equity practices within the sector. As a critique and response to flat and prescriptive EDI plans, what was created based on this cross-country collaboration was a non-linear, spiraling framework existing online that arts organizations can make use of and adapt based on their circumstances. Weaving together a historical account of arts administration, Western managerialism, and the EDI in the arts sector, this article responds to the research question: How can access to the arts and culture sector from coast-to-coast-to-coast be more equitable?